1987
DOI: 10.1139/z87-359
|View full text |Cite
|
Sign up to set email alerts
|

Relative fertility in hybridization experiments using three song types of the held crickets Gryllus integer and Gryllus rubens

Abstract: Species-specific calling songs of male field crickets attract conspecific females. Each wing closure results in a pulse of sound, and the song is composed of pulses arranged in species-specific patterns of short chirps, long continuous trills, or intermediates between chirps and trills. California Gryllus integer has a song with pulses of sound delivered in groups of two or three to produce a chirp, but in central Texas, the G. integer song has a variable number of pulses delivered in long continuous trills. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…Other incompatibilities have been recorded within the genus Gryllus: few eggs hatched when G. rubens and G. assimilis were reciprocally crossed (22), and similar results were obtained when crossing G. rubens and G. pennsylvanicus (22). Bidirectional incompatibility also has been reported between populations of G. rubens and G. integer (17,18) whereas unidirectional incompatibility has been shown between G. ovisopis males and G. firmus females (T. Walker, personal communication). Werren et al (23) reported that G. pennsylvanicus is infected with Wolbachia.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…Other incompatibilities have been recorded within the genus Gryllus: few eggs hatched when G. rubens and G. assimilis were reciprocally crossed (22), and similar results were obtained when crossing G. rubens and G. pennsylvanicus (22). Bidirectional incompatibility also has been reported between populations of G. rubens and G. integer (17,18) whereas unidirectional incompatibility has been shown between G. ovisopis males and G. firmus females (T. Walker, personal communication). Werren et al (23) reported that G. pennsylvanicus is infected with Wolbachia.…”
supporting
confidence: 54%
“…The bidirectional incompatibility observed between G. rubens and G. integer is likely to be the result of infection with the two different strains of Wolbachia found in these two species. The compatibility of G. rubens from Florida with G. integer from Texas (17,18) can be explained because these populations carry the rubens-type bacteria. Our data lend support to the conclusion of Smith and Cade (17) that G. rubens and G. integer from Texas may be the same species, despite differences in their songs of a degree usually used to differentiate species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular phylogenetic evidence indicates that these are sister species (46). Laboratory crosses readily produce hybrid offspring that have fertility equal that of the parental species (47,48) (50,51). On the basis of these two lines of evidence, we tentatively conclude that the two species do not hybridize or do so only rarely.…”
mentioning
confidence: 73%
“…Levels of hybridization are typically measured to estimate reproductive isolation between taxa in sympatry. However, hybridization data alone are often misleading because laboratory and field studies of hybridization can produce very different results (Smith and Cade 1987, Cade and Tyshenko 1990, Gray and Cade 2000 and because these data do not reveal how reproductive isolation is maintained. Therefore, the factors that drive the divergence between closely related taxa in areas of sympatry must be identified.…”
Section: Testing the Hypothesesmentioning
confidence: 99%